The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.17531/ein.2021.2.14
|View full text |Cite
|
Sign up to set email alerts
|

The influence of temperature on the damping characteristic of hydraulic shock absorbers

Abstract: This paper presents the results of bench-tests and calculations assessing the influence of temperature on the performance of a two-pipe hydraulic shock absorber. The shock absorber prepared for the tests was cooled with dry ice to a temperature corresponding to that associated with the average winter conditions in a temperate climate. The temperature range of the shock absorber during testing was ensured via equipping it with a thermocouple and monitoring it with a thermal imaging camera. During testing, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…In a HP strut, as in hydraulic shock absorbers, the vibration energy is dissipated as heat [19]. At high vibration amplitudes and poor heat transfer, this leads to heating of the hydraulic oil and changes in its damping properties [6,8]. In addition, the volume of oil and gas also increases and so does the deflection of the HP strut.…”
Section: Eksploatacja I Niezawodnosc -Maintenance and Reliabilitymentioning
confidence: 99%
“…In a HP strut, as in hydraulic shock absorbers, the vibration energy is dissipated as heat [19]. At high vibration amplitudes and poor heat transfer, this leads to heating of the hydraulic oil and changes in its damping properties [6,8]. In addition, the volume of oil and gas also increases and so does the deflection of the HP strut.…”
Section: Eksploatacja I Niezawodnosc -Maintenance and Reliabilitymentioning
confidence: 99%
“…During the passive suspension process, energy dissipates into the damper oil. The damper will continue to absorb and dissipate heat, which causes its temperature to rise [1][2][3]. The reduction in the damper performance can be attributed to the gradual dissipation of heat in the damper oil.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers from different countries have carried out research into the characteristics of hydraulic shock absorbers. Some of them [4], for example, have studied the effect of low temperatures and others [5][6][7][8][9][10][11][12][13][14][15][16][17][18], in turn, of high temperatures on their damping characteristics. The effect of low temperatures and technical conditions on the characteristics of a hydraulic damper was studied by Z. Hryciow [19].…”
Section: Introductionmentioning
confidence: 99%
“…The effect of low temperatures and technical conditions on the characteristics of a hydraulic damper was studied by Z. Hryciow [19]. Z. Hryciow and others [4] showed that the temperature of a hydraulic shock absorber has a significant effect on the values of the determined damping coefficients. This influence increases as the temperature of the tested shock absorber decreases.…”
Section: Introductionmentioning
confidence: 99%